Management of Ascending Aorta and Aortic Arch: Similarities and Differences Among Cardiovascular Guidelines. (October 2022) - Spanos, Konstantinos; Nana, Petroula; von Kodolitsch, Yskert; Behrendt, Christian-Alexander; Kouvelos, George; Panuccio, Giuseppe; Athanasiou, Thanos; Matsagkas, Miltiadis; Giannoukas, Athanasios; Detter, Christian; Kölbel, Tilo
Background: Ascending aorta and aortic arch diseases have an increasing interest among cardiovascular specialists regarding diagnosis and management. Innovations in endovascular surgery and evolution of open surgery have extended the indications for treatment in patients previously considered unfit for surgery. The aim of this systematic review of the literature was to present and analyze current cardiovascular guidelines for overlap and differences in their recommendations regarding ascending aorta and aortic arch diseases and the assessment of evidence. Methods: The English medical literature was searched using the MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials databases from January 2009 to December 2020. Recommendations on selected topics were analyzed, including issues from definitions and diagnosis (imaging and biomarkers) and indications for treatment to management, including surgical techniques, of the most important ascending aorta and aortic arch diseases. Results: The initial search identified 2414 articles. After exclusion of duplicate or inappropriate articles, the final analysis included 5 articles from multidisciplinary, cardiovascular societies published between 2010 and 2019. The definition of non-A-non-B aortic dissection is lacking from most of the guidelines. There is a disagreement regarding the class of recommendation and level of evidence for the diameter of ascending aorta as an indication. The indication for treatment of aortic disease may be individualized in specific cases while the growth rate may also affect the decision making. The role of endovascular techniques has not been established in current guidelines except by 1 society. Supportive evidence level in the management of aortic arch diseases remains limited. Conclusion: In current recommendations of cardiovascular societies, the ascending aorta and aortic arch remain a domain of open surgery despite the introduction of endovascular techniques. Recommendations of the included societies are mostly based on expert opinion, and the role of endovascular techniques has been highlighted only from 1 society. The chronological heterogeneity apparent among guidelines and the inconsistency in evidence level should be also acknowledged. More data are needed to develop more solid recommendations for the ascending aorta and aortic arch diseases.